What Do You Think about INVALSI Tests? School Directors, Teachers and Students from Lombardy Describe Their Experience - Giulia Pastori; Valentina Pagani (LED Edizioni Universitarie, 2016)
The qualitative study «Promoting the culture of evaluation at school. The INVALSI experience at school» conducted between 2011-2012 by a research team from the University of Milan-Bicocca collected the ideas, opinions and perceptions of school actors on the INVALSI learning assessment experience. Adopting a «multi-vocal perspective», through individual and focus group interviews the viewpoints of different stakeholders within each school (nr. 16) have been examined: school directors (nr. 12), teachers of all grade levels (nr. 106) - some of them referents for the INVALSI evaluation in their school, and middle and high school students (nr. 100) who took INVALSI tests three or four times during their school career. The interpretative hypothesis, confirmed by the present study, considered that the organizational and communication procedures implemented by INVALSI, before and during test administration and correction, and especially during the process of returning the results, have important effects on the perceived quality of national evaluation in schools, on how the tests are proposed to students by school directors and teachers, and ultimately on the students' attitude towards the tests. The experiences collected in this study seem to mirror the antinomy described in literature between accountability and program evaluation, social control and social development objectives. Results highlight the complexity in combining those different approaches, accountability, reflection and self-assessment within the school from a coherent, systemic and procedural viewpoint.